Recognition and Gender Violence: Making Visible Injustice - Strazzeri, Irene (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The article tries to develop a non-conventional narration of gender violence through the description of the career that category of recognition has had both in social sciences and transnational feminist debate. In the first recognition made visible and therefore politically prosecuted asymmetries inherent models of socio-cultural representation of gender relations, in the second it redefined the relationship between equality and difference in the broad debate of social justice. The combination of these results shows that violence against women can be otherwise told provided reading misrecognition as severe form of social injustice.